2008
DOI: 10.1177/0363546508317123
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Comparisons of Anatomic Double-Bundle versus Single-Bundle Anterior Cruciate Ligament Reconstruction Procedures in 328 Consecutive Patients

Abstract: The postoperative anterior and rotational stability after the anatomic double-bundle ACL reconstruction was significantly better than that after the single-bundle reconstruction, although there were no significant differences between the 2 procedures concerning the complications and the clinical evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
300
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(309 citation statements)
references
References 52 publications
(93 reference statements)
6
300
1
2
Order By: Relevance
“…[11][12][13][14][15][16] On the other hand, only a clinical report 17 has introduced a remnant-preserving technique for double-bundle ACL reconstruction, in which 2 femoral tunnels and one tibial tunnel were made, although anatomic double bundle ACL reconstruction procedures have recently attracted notice because of biomechanical advantages in laboratory studies. [18][19][20][21][22][23][24][25][26][27][28] However, no previous studies have shown clinical evidence about utility of the ACL remnant tissue preservation in ACL reconstruction as of yet. To verify whether preservation of the ACL remnant tissue can really improve proprioceptive functions and enhance revascularization, we should conduct a randomized comparative trial with a sufficient number of patients to compare the 2 ACL reconstruction procedures with and without the remnant preservation in terms of proprioception and revascularization of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] On the other hand, only a clinical report 17 has introduced a remnant-preserving technique for double-bundle ACL reconstruction, in which 2 femoral tunnels and one tibial tunnel were made, although anatomic double bundle ACL reconstruction procedures have recently attracted notice because of biomechanical advantages in laboratory studies. [18][19][20][21][22][23][24][25][26][27][28] However, no previous studies have shown clinical evidence about utility of the ACL remnant tissue preservation in ACL reconstruction as of yet. To verify whether preservation of the ACL remnant tissue can really improve proprioceptive functions and enhance revascularization, we should conduct a randomized comparative trial with a sufficient number of patients to compare the 2 ACL reconstruction procedures with and without the remnant preservation in terms of proprioception and revascularization of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…When accounting for the literature comparing singleand double-bundle ACL reconstruction, improved postoperative laxity and outcome scores for double-bundle ACL reconstruction have been reported in several in vivo studies [11,42,43]. However, other studies have shown no significant differences between these techniques [44][45][46].…”
Section: Double-bundle Acl Reconstructionmentioning
confidence: 99%
“…Kondo et al found that double bundle reconstruction was better than non-anatomic single bundle however there was no difference compared to a laterally placed anatomical single bundle. They concluded that double bundle reconstruction may not offer a significant advantage over single bundle [38]. Ho et al showed equal kinematics using central anatomic single bundle compared to double bundle reconstruction [39].…”
Section: Biomechanical Studiesmentioning
confidence: 99%
“…Given the biomechanical advantages of performing double bundle ACL reconstruction over non-anatomic single bundle reconstruction it is not surprising that there have been numerous clinical studies comparing double and single bundle ACL reconstruction [38,[41][42][43][44][45][46][47]. Several of these reveal improved anterior and rotational stability with DB reconstruction [38,43,45,47] however many show no significant difference [42,44,46].…”
Section: Clinical Outcomesmentioning
confidence: 99%